Analisis Status Kerusakan Tanah Berbasis Sistem Informasi Geografis (SIG) di Daerah Aliran Sungai Yeh Ho Kabupaten Tabanan - ALDINO RYAN FAUZI; NI MADE TRIGUNASIH; I WAYAN NARKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Soil Damage Status Analysis Based on Geographical Information System (GIS) In Yeh Ho Watershed Tabanan Regency The study aims to identify land damage status at DAS Yeh Ho, map land damage status at DAS Yeh Ho, and provide improvements soil condition recommendations on DAS Yeh Ho. Research methods is a survey method, land unit map is made for field sampling purposes. Based on the results overlay slope map, land type map, rainfall map and usage map get 13 samples. Results of samples that have been collected in the analysis in the laboratory to determine the content value of content weight, solum thickness, surface kerocks, fraction composition, total porosity, electrical power, pH, and permeability. This research shows that there is a land use influence on soil damage status. The results of the research on the state of soil damage is good in SLH 1, 2, 5.7, 8, and 12 with N symbol, the data of damaged soil damage status is in SLH 6, 10 and 13. Mild damaged Status in SLH is caused by texture and permeability with symbol R. I – F, p. SLH 3, 4, 9, and 11 entered into mild damaged category, permeability with symbol R. I – P. Recommendation results of this research is the improvement of the permeability parameters by means of planting annual crops and the addition of organic materials.